Insights Into Leukocyte Trafficking in Inflammatory Arthritis – Imaging the Joint - Manning, Julia E.; Lewis, Jonathan W.; Marsh, Lucy-Jayne; McGettrick, Helen M. (Frontiers in Cell and Developmental Biology, 2021)
The inappropriate accumulation and activation of leukocytes is a shared pathological feature of immune-mediated inflammatory diseases (IMIDs), such as rheumatoid arthritis (RA) and psoriatic arthritis (PsA). Cellular accumulation is therefore an attractive target for therapeutic intervention. However, attempts to modulate leukocyte entry and exit from the joint have proven unsuccessful to date, indicating that gaps in our knowledge remain. Technological advancements are now allowing real-time tracking of leukocyte movement through arthritic joints or in vitro joint constructs. Coupling this technology with improvements in analysing the cellular composition, location and interactions of leukocytes with neighbouring cells has increased our understanding of the temporal dynamics and molecular mechanisms underpinning pathological accumulation of leukocytes in arthritic joints. In this review, we explore our current understanding of the mechanisms leading to inappropriate leukocyte trafficking in inflammatory arthritis, and how these evolve with disease progression. Moreover, we highlight the advances in imaging of human and murine joints, along with multi-cellular ex vivo joint constructs that have led to our current knowledge base.